ChemInform Abstract: Approach to cis‐Phlegmarine Alkaloids via Stereodivergent Reduction: Total Synthesis of (+)‐Serratezomine E and Putative Structure of (‐)‐Huperzine N. Issue 10 (February 2016) - Bosch, Caroline; Fiser, Bela; Gomez‐Bengoa, Enrique; Bradshaw, Ben; Bonjoch, Josep
Abstract: Based on the executed total syntheses the structure of natural huperzine N is reassigned to (III), a diastereomer of (II).